An investigation into the effectiveness of statistical process control techniques, with management data from a product development environment - Julien, Denyse (1998)
The study reported on in this thesis was an empirical investigation into the implementation and use of, Statistical Process Control (SPC) techniques and tools in a product development environment. The data used originated from four different business units in the European flavour division of a large International company, belonging to the Flavour and Fragrance industry. The study highlights many of the problems related to the use of real data, and working with individuals throughout an organisation.